Motives for using Instagram Among Young Adults - D, Amudhu (Journal of Advanced Research in Journalism & Mass Communication, 2023)
The research article would be analyzing movies using Instagram among 18-26 years of young adults. The rise of social media platforms has led to various advanced needs. The study chose 103 samples to assess the different factors such as physiological needs, safety needs, love and belonging needs, esteem needs, and self-actualization. Based on the analysis, female users were more compared to male players. Users of Instagram, feel happy when they chat with their friends. Though many factors the motive to share your personal information with others male participants students expressed higher levels of agreement than female students whereas in all other five other female participants students expressed higher levels of agreement than male participants. How to cite this article: Amudhu D. Motives for using Instagram Among Young Adults. J Adv Res Jrnl Mass Comm 2022; 9(4): 6-9. DOI: https://doi.org/10.24321/2395.3810.202208